Pengaruh Kebijakan Partisipasi Masyarakat Terhadap Environmental Quality di Kota Lubuklinggau - Karina, Helda; Saputra, Wendi Aji; Suramto, Suramto (Jurnal Publisitas, 2024)
This research aims to identify factors that lead to low community participation and to find out how much influence the community participation policy of Siring Agung Village has on environmental quality. This research is a quantitative study using a descriptive approach, with the independent variable being community participation and the dependent variable being environmental quality. There are 276 samples in this study. The data analysis technique used in testing the hypothesis in the study is to use simple linear regression analysis technique to determine the effect of community participation (X) as an independent variable on environmental quality (Y) as the dependent variable. The results showed a correlation between variable X (community participation) and variable Y (environmental quality). This is evidenced by testing simple linear regression analysis to get the equation Y = 4.160 + 0.433 X, and it is produced by the t-test that the tcount = 22.725> from the ttable value = 1.650 with a significance level of less than 0.05 and the coefficient of determination shows that the community participation variable (X) has an influence of 65.3% on environmental quality (Y), this states that the pearson correlation value produced is interpreted as strong and the remaining 34.7% is influenced by other factors and Furthermore, the F test has a calculated F value of 516 . 442> F table 3.88 so this shows that the independent variable simultaneously affects the dependent variable.